Correcting for tool decentralization of oriented six-arm caliper logs for determination of contemporary tectonic stress orientation - Wagner, D.; Muller, B.; Tingay, Mark (Society of Petrophysics & Well Log Analysts, 2004)
Tool decentralization is a major problem in the analysis of six-arm caliper data, particularly in highly deviated wells. It precludes accurate determination of borehole geometry and hence, interpretation of borehole volume, stratigraphic horizons and present-day stress orientation. We test four methods for correcting tool decentralization of six-arm caliper data, for the primary purpose of interpreting present-day stress orientations from borehole breakouts. The ''chord approach'' and ''ellipse algorithm'' yielded the most accurate corrections for tool decentralization in real and modeled scenarios of breakouts, key-seats and in-gauge holes.